Reducing Visual Descriptor Scale (VDS) in Dysminorrhea on Adolescence by Giving Wood Secang Boiled Water (Caesalpinia Sappan L) in Megarezky University - Sampara, Nurqalbi; Nurhidayat Triananinsi; Rosita Passe; Jumrah Sudirman (Publisher Cv. Inara, 2020)
Dysmenorrhea is the pain experienced during menstruation that causes women to experience varying degrees of cramps. It presents as discomfort, while others suffer pain that can stop daily activities for some women. Therefore, to reduce the use of drugs, herbal methods are used, boiled water for the wood secang, so that side effects can minimize for the body. This research aims to analyze the reduction of Visual Descriptor Scale (VDS) of adolescence with dysmenorrhea in Makassar. This research lasted for one year with several stages, including the first stage; identify research samples based on criteria. The second stage, making informed consent and choice of respondents. The third stage, using a Quasi-Experimental design with a pretest and post-test approach in one treatment group, namely adolescents with dysmenorrhea, measured VDS before giving the boiled water for secang wood and after giving it. The fifth stage, assessing the decrease of VDS before and after treatment. This study indicated that the average intensity of the respondents' menstrual pain before giving the boiled water of secang wood was 4.5, where the lowest menstrual pain intensity was two. The highest was 8, while after giving secang wood boiled water was 3.0, where the pain intensity was the lowest menstrual period was 0, and the highest was 6. The Paired T-Test results obtained a p-value of 0.000 <0.05 so that the boiled water of secang wood affects reducing pain intensity in young females.